Implementation of Syamil and Dodo Animated Audio Visual Media to Improve Receptive Language Development of 4-5 Year Old Children at Quantum Cendikia Kindergarten - Busana, Busana; Musayyadah, Musayyadah; Siti farida (Penerbit Hellow Pustaka, 2025)
This study aims to describe the implementation of the Syamil and Dodo animated audio-visual media in improving receptive language skills of children aged 4–5 years at TK Quantum Cendikia. The research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving teachers and students. The findings reveal that the use of Syamil and Dodo animation effectively enhances five key aspects of receptive language: listening to others, understanding two-step instructions, comprehending story content, recognizing new vocabulary, and distinguishing sounds in the Indonesian language. This media successfully captures children's attention, creates a more engaging learning atmosphere, and encourages active participation throughout the learning process. Thus, animated audio-visual media can be considered an effective alternative to support the development of receptive language skills in early childhood education.